The Impact of Internal Organizational Culture on Employee Retention - Hajizada, Farid; Černá, Daniela; Hořáková, Marie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This thesis explores the concept, values, and types of internal organizational culture and how they affect employee retention. It analyzes how the global IT company IBM has structured its internal organizational culture, which it uses to retain and develop its employees. The author primarily focused on the structure of the IBM company as well as its six principles of culture in the organization. The analysis was carried out through a survey. As for the participants, the author randomly selected 50 IBM employees in Prague, during which the following points were noted: Although a significant proportion of IBM's workforce expresses contentment with the company's organizational culture and its approach to employee development and career advancement, there remain individuals who believe that the level of organizational culture could be enhanced. For this purpose, ways to improve their methods of maintaining organizational culture are considered. The author suggested possible solutions in favor of increasing the value of organizational culture for employees.
Vedoucí práce: Daniela Černá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses